2014
DOI: 10.1080/00986445.2014.934449
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Isotherms, Thermodynamics, and Kinetic Studies for the Adsorption of Food Azo Dyes onto Chitosan Films

Abstract: The adsorption of FD&C red 2 and FD&C yellow 5 onto chitosan films was evaluated by equilibrium isotherms, thermodynamics and kinetic studies. The effects of temperature (298-328 K), initial dye concentration (50-300 mg L -1 ), stirring rate (50-350 rpm) and contact time (0-120 min) were investigated at pH of 2.0 and 100 mg L -1 of chitosan films. The dyes concentration was determined by spectrophotometry. Freundlich and Langmuir models were used to represent the equilibrium data. The Langmuir model was the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(4 citation statements)
references
References 32 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Particle size can be obtained using scanning electron microscopy (SEM), sieving test, or using a particle size analyzer. The effect of the particle size, surface area, and pore volume of chitosan on the adsorption of some food azo dyes FD&C red 2 and FD&C yellow 5 was studied before [37]. The particle sizes used were 0.10, 0.18, and 0.26 mm with surfaces of 4.2, 3.4, or 1.6 m 2 /g.…”
Section: Surface Area and Particle Size Featuresmentioning
confidence: 99%
“…Particle size can be obtained using scanning electron microscopy (SEM), sieving test, or using a particle size analyzer. The effect of the particle size, surface area, and pore volume of chitosan on the adsorption of some food azo dyes FD&C red 2 and FD&C yellow 5 was studied before [37]. The particle sizes used were 0.10, 0.18, and 0.26 mm with surfaces of 4.2, 3.4, or 1.6 m 2 /g.…”
Section: Surface Area and Particle Size Featuresmentioning
confidence: 99%
“…The kinetic fitting results showed the arrival of the adsorbate from the solution to the adsorbent surface was controlled by surface diffusion, and the only factor that determined the adsorption rate was the concentration of NH + 4 -N because the temperature had little effect. Several research papers have reported the same conclusion that the pseudofirst-order kinetics was more consistent with the adsorption process (Cadaval et al 2015;Guo et al 2019;Hu et al 2020).…”
Section: Adsorption Kinetic Studiesmentioning
confidence: 76%
“…The equilibrium data were further analyzed by Langmuir and Freundlich isotherm models, respectively (Cadaval et al 2015).…”
Section: Effect Of Adsorbate Concentration and The Isotherms Of The Adsorptionmentioning
confidence: 99%